Putusan Nomor 8/g/2020/pt.tun.jkt : Analisis Yuridis Upaya Administratif Dalam Menyelesaikan Sengketa Kepegawaian - Mayluvinda, Eufrosina Kasyitha; Aurellia, Ixora Andini (Universitas Kapuas, 2024)
Civil servants play an important role because they are part of the state apparatus that carries out government and development in order to achieve state goals. Enforcing discipline, especially among civil servants, is the first step towards realizing a clean and authoritative government. Personnel disputes at the State Administrative Court (PTUN) are a major concern in the context of administrative law enforcement. The judicial process and the resulting decisions have a significant impact on organizational sustainability and employee welfare. The research method used is normative juridical. With the enactment of the Government Administration Law, the absolute competence of Administrative Justice was expanded not only to include testing and examining decisions, but also testing and assessing the factual actions of government organs as well as determine whether there are elements of abuse of authority committed by government officials. However, as several people have pointed out above, the development of absolute competence raises legal problems that are difficult to resolve. The ruling shows that administrative efforts are not finfing a win-win solution for both parties.